Fundamentos lingüísticos de la indización: una revisión Linguistic fundamentals of indexing: a review - Martines, Alexandre Robson [UNESP]; Almeida, Carlos Candido [UNESP] (Univ Zaragoza, 2023)
The stages of the indexing process demand from the professional technical, specific and specialized knowledge about the practice itself, in addition to the scientific or cultural universe inherent to the material to be classified and indexed. Terminological aspects are fundamental inputs for the elaboration of documentary language; the analysis of language becomes a neces-sary approach, since the study of language through lin-guistics and philosophy of language has shown a lot of evolution in recent years. The aim of this research is to discuss the indexing process and analyze fundamen-tals of linguistics and the philosophy of language that can contribute to the epistemological-logical under-standing of the layers of knowledge that involve the en-tire indexing path. A qualitative, exploratory and biblio-graphic methodology was applied. The tradition inher-ent to indexing made possible, among so many mod-els, the interrogative pronouns, the notional aspects, facets, however the modal aspects lead the indexing format, since the strategy behind the formatting of the modals in the treatment of information is the model that impacts on the user behavior when carrying out searches.
Keywords: Indexing; Linguistics; Modals; Linguistic fundamentals